Clasterization Of Data Using Contraceptive Equipment At Puskesmas Kampung Bali, Bengkulu City Using K-Means Method - Prara Sindia Citra Tessa; Liza Yulianti; Herlina Latipa Sari (Jurnal Komputer, Informasi dan Teknologi, 2022)
Kampung Bali Health Center is one of the health centers in Bengkulu City. The health center serves the family planning program by providing contraceptives, such as pills, injections, condoms, IUDs, and implants. The data processing on supplies and expenditures of contraceptives is done manually by filling in the form provided. It will be recapitulated by the officer to know the use of contraceptives for 1 year. Unfortunately, this procedure is not efficient because it takes time and sometimes there are miscalculations that cause errors in determining the supply of contraceptives. Moreover, the health center needs data on most in demand and least desirable contraceptives. The application of data clusterization on contraceptive use at the Kampung Bali Health Center in Bengkulu City is used to assist the Health Center in managing monthly contraceptive data, and to assist the Health Center in finding out which contraceptive information is most in demand and the least desirable. The K-Means Clustering methodology applied in this research is used in order to divide the contraceptive data into 2 groups; Cluster C1 (the most popular) and Cluster C2 (the least desirable) based on an analysis of the amount of supply and use of contraceptives. There are 60 participants in this study, where Cluster C1 consisted of 24 data and Cluster C2 consisted of 36 data, with the percentage value of C1 clustering 40% and C2 60%. Based on the test, it shows that the functional application of clustering data on contraceptive use at the Kampung Bali Health Center in Bengkulu is running well. It also give beneficial information about data clasterization of contraceptives.